Ruxolitinib solid lipid nanoparticles and preparation method thereof
Through solid lipid nanoparticles technology, the preparation of rusotinib nanoparticles with small particle size and high stability was solved, and the existing rusotinib creams had large particle size and low stability, significantly improved the transdermal ability and retention of the drug, thereby enhancing the therapeutic effect of vitiligo.
Patent Information
- Application Number
- CN202411068303.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-08-06
AI Technical Summary
The existing Rusotinib cream has a large particle size and low stability, resulting in less drug permeability and skin retention, affecting the treatment effect.
Solid lipid nanoparticles (SLN) were used as nanocarriers to load rusotinib, and solid lipid nanoparticles were prepared by melt emulsification-ultrasonic method, and the particle size, coating material and surfactant ratio was adjusted to improve the stability and drug loading of nanoparticles.
It significantly improved the transdermal ability and skin retention of rusotinib, and enhanced its therapeutic effect on vitiligo.
Smart Images

Figure CN118986930B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of pharmaceutical preparations, and in particular to ruxolitinib solid lipid nanoparticles and a preparation method thereof. Background Art
[0002] Vitiligo is a chronic autoimmune disease characterized by local or systemic skin depigmentation and white patches due to the loss of melanocytes. The pathogenesis of vitiligo is still unclear, and the main theories include genetic causes, autoimmune mechanisms, and oxidative stress. There are currently four main treatments for vitiligo: topical preparations, phototherapy, oral preparations, and skin transplantation. Among them, skin transplantation is less used; phototherapy requires hospitalization, and patient compliance is poor; oral preparations have relatively large adverse reactions, so topical preparations are usually used for treatment.
[0003] Ruxolitinib (Ru) is a selective protein tyrosine kinase (Janus kinase, JAKs) inhibitor that can selectively inhibit JAK1 and JAK2, prevent cytokines or other molecules mediated by JAKs from transmitting external signals to the cell nucleus, and significantly regulate the enrichment of inflammatory factors and chemokines of immune function stress, thereby inhibiting the abnormal immune function of vitiligo patients. Ruxolitinib cream (Ru-Cream) is a topical medication made of ruxolitinib, a small molecule tyrosine kinase inhibitor, which can inhibit intracellular signaling pathways and help restore normal skin pigmentation. Although Ru-Cream has shown good results in clinical trials, it still has many limitations that need further research and optimization. For example, the current Ru-Cream has a large particle size and low stability, resulting in less drug penetration and skin retention, which will lead to reduced efficacy and have a certain impact on the treatment of vitiligo.
[0004] Solid lipid nanoparticles (SLN) are a new generation of submicron drug delivery systems developed in the early 1990s. They have potential advantages over traditional dosage forms, such as smaller particle size for targeted drug delivery to the skin, prolonged drug release time at skin targets, increased stability of encapsulated drugs, improved solubility of poorly soluble drugs, and improved bioavailability. Using solid lipid nanoparticles as nanocarriers to load ruxolitinib is expected to improve the transdermal ability and skin retention of ruxolitinib, thereby improving its vitiligo treatment effect and providing a theoretical basis for the development of its preparations. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a ruxolitinib solid lipid nanoparticle, which has a small particle size, high stability, encapsulation efficiency and drug loading, and significantly improves the skin penetration ability and skin retention of ruxolitinib for transdermal administration.
[0006] The purpose of the present invention is to provide a ruxolitinib solid lipid nanoparticle, which has ruxolitinib as the core and is coated with a coating material on the surface. The coating material includes a lipid material, and the mass ratio of ruxolitinib to the lipid material is 1:(3.5-7).
[0007] In an optional embodiment, the coating material includes a lipid material and a surfactant, and the mass ratio of ruxolitinib, the lipid material and the surfactant is 1:(3.5-7):(5-14).
[0008] In an optional embodiment, the lipid material includes fatty acids and phospholipids, and the mass ratio of the fatty acids to the phospholipids is (1-2): (2.5-5).
[0009] In an optional embodiment, the fatty acid material is selected from one or both of lauric acid and stearic acid.
[0010] In an optional embodiment, the phospholipid material is selected from one or both of soybean lecithin and egg yolk lecithin.
[0011] In an alternative embodiment, the surfactant includes any one or both of PEG-40 hydrogenated castor oil or TPGS.
[0012] Another object of the present invention is to provide a method for preparing ruxolitinib solid lipid nanoparticles, comprising the following steps: step 1, heating and melting ruxolitinib and fatty acid materials to mix and prepare an oil phase; step 2, using an aqueous solution of phospholipid materials and surfactants as an aqueous phase; step 3, adding the aqueous phase to the oil phase to prepare colostrum; step 4, cooling and solidifying the colostrum after ultrasonication, then fixing the volume, and filtering to prepare ruxolitinib solid lipid nanoparticles.
[0013] In an optional embodiment, in the step 1, heating and melting are carried out under magnetic stirring, the rotation speed of the magnetic stirring is 500-1500 r / min, and the heating temperature is 65-85°C; in the step 2, the aqueous solution of the phospholipid material and the surfactant is specifically obtained by dissolving the phospholipid material and the surfactant in water, and the dissolution temperature is 65-85°C.
[0014] In an optional embodiment, in step 3, the specific steps of adding the water phase to the oil phase are: slowly dripping the water phase into the oil phase at 65-85°C with stirring, the dripping time is 0-10 min, and the stirring is continued for 15-30 min, and the stirring speed is 500-1500 r / min.
[0015] In an optional embodiment, in step 4, the ultrasonic time is 0 to 15 min, the ice bath solidification time is 5 to 15 min, the volume is fixed to 10 to 20 mL, and the pore size of the filtration is 0.1 to 0.3 μm.
[0016] The present invention has the following beneficial effects:
[0017] The present invention utilizes solid lipid nanoparticles to encapsulate ruxolitinib, which has a small particle size, moderate PDI, high encapsulation rate and drug loading, and can effectively exert the effect of ruxolitinib in treating skin diseases such as vitiligo and atopic dermatitis. Compared with traditional cream dosage forms, ruxolitinib solid lipid nanoparticles can improve the permeability and permeation amount of transdermal delivery, providing convenience for a large number of patients with skin diseases. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The drug precipitation conditions under microscope of different solid lipids of the present invention;
[0019] Figure 2 is an absorbance graph of the solubilization ability of different surfactants of the present invention on lauric acid;
[0020] Figure 3 This is the appearance diagram of Ru-SLN of the present invention;
[0021] Figure 4 is a particle size diagram of Ru-SLN of the present invention;
[0022] Figure 5 This is a graph showing the in vitro release rate of Ru-SLN of the present invention;
[0023] Figure 6 This is a diagram showing the in vitro skin penetration effect of Ru-Cream and Ru-SLN of the present invention;
[0024] Figure 7 This is a graph of in vitro skin retention of Ru-Cream and Ru-SLN of the present invention;
[0025] Figure 8 The in vitro skin permeation and total retention of Ru-Cream and Ru-SLN of the present invention;
[0026] Fig. 9 This is a graph showing the weight changes of mice in different groups of the present invention;
[0027] Fig.10This is a map of vitiligo lesion areas in different groups of mice in the present invention. DETAILED DESCRIPTION
[0028] The present invention is further described below with reference to the examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0029] Example 1
[0030] 80 mg of Ruxolitinib (Ru) and 80 mg of lauric acid were accurately weighed and placed in a 50 mL conical beaker, heated and melted at 75°C and 1000 min / r under magnetic stirring to obtain an oil phase; 750 mg of PEG-40 hydrogenated castor oil and 300 mg of soybean lecithin were accurately weighed and placed in a 50 mL EP tube, 15 mL of ultrapure water was added and stirred at 75°C to dissolve and mix the PEG-40 hydrogenated castor oil and soybean lecithin to obtain an aqueous phase; the aqueous phase was slowly dripped into the oil phase at 1000 min / r and 75°C for 5 min, and the stirring was continued for 20 min to obtain colostrum; the colostrum was ultrasonicated at room temperature (power: 80%, on: 5s, off: 5s) for 10 min, then placed in an ice bath for solidification for 10 min, and then the volume was adjusted to 20 mL, and filtered through a 0.22 μm micropore filter to obtain Ru-SLN (Ruxolitinib solid lipid nanoparticles).
[0031] Example 2
[0032] The difference between this embodiment and embodiment 1 is that 120 mg of lauric acid, 200 mg of soybean lecithin, and 1050 mg of PEG-40 hydrogenated castor oil are added, and the other details are the same as those in embodiment 1.
[0033] Example 3
[0034] The difference between this embodiment and embodiment 1 is that 160 mg of lauric acid, 400 mg of soybean lecithin, and 450 mg of PEG-40 hydrogenated castor oil are added, and the other details are the same as those in embodiment 1.
[0035] Example 4
[0036] The difference between this embodiment and embodiment 1 is that the fatty acid material is stearic acid, and the added amount is 80 mg. Other details are the same as embodiment 1.
[0037] Example 5
[0038] The difference between this embodiment and embodiment 1 is that the fatty acid material is stearic acid, and the added amount is 120 mg. Other details are the same as embodiment 1.
[0039] Example 6
[0040] The difference between this embodiment and embodiment 1 is that the fatty acid material is stearic acid, and the added amount is 160 mg. Other details are the same as embodiment 1.
[0041] Example 7
[0042] The difference between this embodiment and embodiment 1 is that the phospholipid material is egg yolk lecithin, and the added amount is 300 mg. Other details are the same as embodiment 1.
[0043] Example 8
[0044] The difference between this embodiment and embodiment 1 is that the phospholipid material is egg yolk lecithin, and the added amount is 200 mg. Other details are the same as embodiment 1.
[0045] Example 9
[0046] The difference between this embodiment and embodiment 1 is that the phospholipid material is egg yolk lecithin, and the added amount is 400 mg. Other details are the same as embodiment 1.
[0047] Example 10
[0048] The difference between this embodiment and embodiment 1 is that the surfactant is TPGS, and the added amount is 750 mg. Other details are the same as embodiment 1.
[0049] Embodiment 11
[0050] The difference between this embodiment and embodiment 1 is that the surfactant is TPGS, and the added amount is 1050 mg. Other details are the same as embodiment 1.
[0051] Example 12
[0052] The difference between this embodiment and embodiment 1 is that the surfactant is TPGS, and the added amount is 450 mg. Other details are the same as embodiment 1.
[0053] 1. Process research of Ruxolitinib solid lipid nanoparticles (Ru-SLN)
[0054] (I) Screening of single factors in preparation process
[0055] 1. Screening of preparation methods
[0056] The effects of thin film hydration and melt emulsification-ultrasound methods on the preparation of Ru-SLN were investigated using particle size, PDI (polydispersity index), and encapsulation efficiency as indicators. The steps for preparing Ru-SLN by thin film hydration and melt emulsification-ultrasound methods are as follows:
[0057] Preparation of Ru-SLN by thin film hydration method: Accurately weigh appropriate amounts of lauric acid and soybean lecithin into a round-bottom flask, add anhydrous ethanol to fully dissolve them; accurately weigh an appropriate amount of Ru, dissolve it in anhydrous ethanol, pour it into the round-bottom flask and mix it evenly, remove the anhydrous ethanol by rotary evaporation in a 55°C water bath on a rotary evaporator to form a uniform thin film of lipid inside the round-bottom flask, pour an appropriate amount of PEG-40 hydrogenated castor oil solution into it, hydrate it at the same temperature, ultrasonicate it in an ultrasonic cleaner for a suitable time, and homogenize it three times at 24000psi on a high-pressure microfluidizer to obtain Ru-SLN.
[0058] Preparation of Ru-SLN by melt emulsification-ultrasound method: Accurately weigh appropriate amount of Ru and lauric acid, heat and stir at 75°C to melt, and obtain oil phase; accurately weigh appropriate amount of PEG-40 hydrogenated castor oil and soybean lecithin, dissolve and mix in ultrapure water, and obtain water phase. After the water phase is heated to the same temperature as the oil phase, slowly drip it into the oil phase and stir at a constant rate to obtain colostrum; after the colostrum is ultrasonicated at room temperature, place it in an ice bath to solidify for a period of time, and Ru-SLN is obtained.
[0059] The results show that both methods can successfully prepare Ru-SLN, the solution is relatively uniform, and it presents a light blue fluorescence. Among them, the Ru-SLN prepared by the thin film hydration method has a particle size of (39.257±3.919)nm, PDI (0.281±0.001), and an encapsulation rate of (98.579±0.569)%; the Ru-SLN prepared by the melt emulsification and ultrasound method has a particle size of (40.033±0.295)nm, PDI (0.235±0.003), and an encapsulation rate of (95.679±0.419)%. Since the melt emulsification and ultrasound method does not add organic solvents during preparation and has a high preparation efficiency, the melt emulsification and ultrasound method was finally selected as the preparation method of Ru-SLN.
[0060] 2. Screening of the dripping time
[0061] The effect of different addition times of the aqueous phase into the oil phase on Ru-SLN was investigated using particle size, PDI (polydispersity index), and encapsulation efficiency as indicators. The other preparation methods were fixed unchanged, and the addition speed was controlled within 0 min, 5 min, and 10 min when the aqueous phase was dropped into the oil phase. The results are shown in Table 1.
[0062] Table 1 Effect of different dropping time on Ru-SLN particle size, PDI and encapsulation efficiency (n=3)
[0063] Dropping time / min Particle size / nm PDI Encapsulation rate / % 0 43.523±3.387 0.258±0.013 95.951±1.831 5 41.584±2.831 0.248±0.011 97.011±1.230 10 44.739±3.412 0.249±0.022 95.730±2.128
[0064] The results show that the drop time within 0min~10min has little effect on the particle size, PDI and encapsulation rate of Ru-SLN. When the drop time is 0min, the prepared Ru-SLN still has a smaller particle size, PDI and a higher encapsulation rate. The reason for this result may be that the power is too high or the time is too long during ultrasound. Higher ultrasonic energy may eliminate the influence of uneven dispersion of the oil phase during the preparation of colostrum. In order to ensure the quality of Ru-SLN, the drop time was finally selected as 5min.
[0065] 2. Screening of stirring time
[0066] Taking particle size, PDI and encapsulation efficiency as indicators, the effects of different stirring times on Ru-SLN were investigated.
[0067] Keeping other preparation methods unchanged, the colostrum stirring time was controlled at 15 min, 20 min, and 25 min respectively to examine the effect on Ru-SLN. The results are shown in Table 2.
[0068] Table 2 Effect of different stirring times on Ru-SLN particle size, PDI, and encapsulation efficiency (n=3)
[0069] Stirring time / min Particle size / nm PDI Encapsulation rate / % 15 39.239±0.682 0.242±0.013 96.349±0.500 20 41.584±2.831 0.248±0.011 97.011±1.230 25 39.764±0.773 0.248±0.007 96.241±1.011
[0070] The results show that the stirring time within 15min to 25min has little effect on the particle size, PDI and encapsulation efficiency of Ru-SLN. In order to improve the experimental efficiency, the stirring time was finally selected as 20min.
[0071] 3. Screening of ultrasound time
[0072] Taking particle size, PDI and encapsulation efficiency as indicators, the effects of different ultrasonic times on Ru-SLN were investigated.
[0073] The other preparation methods were kept unchanged, and the effects on Ru-SLN were investigated by controlling the ultrasonic time at 0 min, 5 min, and 10 min. The results are shown in Table 3.
[0074] Table 3 Effect of different ultrasonic time on Ru-SLN particle size, PDI and encapsulation efficiency (n=3)
[0075] Ultrasonic time / min Particle size / nm PDI Encapsulation rate / % 5 50.038±6.175 0.264±0.019 96.952±0.599 10 41.564±2.831 0.248±0.011 97.011±1.230 15 39.744±1.014 0.230±0.016 95.831±0.988
[0076] The results showed that the ultrasonic time was negatively correlated with the particle size and PDI of Ru-SLN, and the ultrasonic time could change the particle size and dispersion uniformity of SLN. Finally, the ultrasonic time of 10 min was selected, with moderate particle size and PDI and high encapsulation efficiency.
[0077] 4. Screening of curing time
[0078] The effects of different ice bath curing times on Ru-SLN were investigated using particle size, PDI, and encapsulation efficiency as indicators. The other preparation methods were fixed unchanged, and the effects on Ru-SLN were investigated when the ice bath curing time was controlled at 0 min, 5 min, and 10 min. The results are shown in Table 4.
[0079] Table 4 Effect of different curing time on Ru-SLN particle size, PDI and encapsulation efficiency (n=3)
[0080] Curing time / min Particle size / nm PDI Encapsulation rate / % 0 39.839±1.887 0.245±0.010 97.154±0.084 10 41.584±2.831 0.248±0.011 97.011±1.230 20 38.058±0.686 0.244±0.007 96.012±1.324
[0081] The results show that the curing time within 0min~20min has little effect on the particle size, PDI and encapsulation efficiency of Ru-SLN. Increasing the curing time may increase the SLN encapsulation efficiency and stability. However, in this experiment, the Ru-SLN encapsulation efficiency was already high when the curing time was 0min, and increasing the curing time had no significant effect on the encapsulation efficiency. However, in order to ensure the stability of Ru-SLN, the final curing time was selected as 10min.
[0082] (II) Screening of single factors of prescription and process
[0083] 1. Preliminary screening of solid lipids (fatty acids)
[0084] Taking the solubility of Ru as an index and keeping other components unchanged, the effects of 11 solid lipids including lauric acid, palmitic acid, stearic acid polyethylene glycol glyceride, glyceryl monostearate, glyceryl distearate, glyceryl tristearate, hexadecanol, cetearyl alcohol, glyceryl mono / distearate, and glyceryl behenate on the preparation of Ru-SLN were investigated.
[0085] 500 mg each of 11 kinds of solid lipids including lauric acid, palmitic acid, stearic acid, stearic acid macrogol glyceride, glyceryl monostearate, glyceryl distearate, glyceryl tristearate, cetyl alcohol, cetearyl alcohol, glyceryl mono / distearate, and glyceryl behenate were accurately weighed and melted at 75°C. Ru was added to each solid lipid in small amounts and multiple times, heated at 75°C and vortexed appropriately to fully dissolve it until the saturated solubility was reached and no more Ru could be dissolved and a small amount of Ru precipitated.
[0086] The solubility of Ru in different lipids was observed visually and the amount of Ru added to different solid lipids was counted. After each addition of Ru, temporary sections were prepared. After cooling at room temperature, the drug dissolution and drug precipitation were observed under a polarized light microscope. Based on the amount of Ru added to different lipids and the drug dissolution and drug precipitation under the microscope, the solid lipid with better Ru solubility was selected. The amount of Ru that can be dissolved in 11 different solid lipids is shown in Table 5. The drug dissolution and drug precipitation under the microscope are shown in Table 5. Figure 1 shown.
[0087] Table 5 Addition amount of Ru in different solid lipids
[0088]
[0089] The results showed that lauric acid had the highest solubility for Ru (>150mg); followed by palmitic acid and stearic acid (120mg-150mg); glyceride solid lipids had poor solubility for Ru (<100mg).
[0090] exist Figure 1 In the present invention, A and B are Ru powders, which are multi-colored crystals; glyceryl behenate (I) reaches saturation when the dosage is 10 mg, and obvious drug crystal forms (J) can be seen visually and under a microscope; glyceryl distearate (K), glyceryl tristearate (M), hexadecanol (O), cetearyl alcohol (Q), and glyceryl mono / distearate (S) reach saturation when the dosage is 30 mg, and obvious drug crystal forms (L), (N), (P), (R), and (T) can be seen visually and under a microscope; glyceryl monostearate Ester (U) reaches saturation when the dosage is 60 mg, and obvious drug crystal form (V) can be seen under visual microscope; stearic acid polyethylene glycol glyceride (W) reaches saturation when the dosage is 90 mg, and obvious drug crystal form (X) can be seen under visual microscope; when the total amount of drug added is 150 mg, a small amount of drug has been precipitated from palmitic acid and stearic acid under visual observation, and lauric acid can still completely dissolve the drug. Since lauric acid, palmitic acid, and stearic acid themselves are multi-color crystals, it is difficult to distinguish whether there is drug precipitation under a microscope. However, combined with the amount of drug added, visual observation, and microscope images, lauric acid, palmitic acid, and stearic acid were selected as solid lipids to further prepare Ru-SLN.
[0091] It should be noted that in Figure 1 In the figure, Ru control (A, B); lauric acid control (C) and precipitation (D); stearic acid control (E) and precipitation (F); palmitic acid control (G) and precipitation (H); behenic acid glyceryl control (I) and precipitation (J); distearic acid glyceryl control (K) and precipitation (L); tristearic acid glyceryl control (M) and precipitation (N); hexadecanol control (O) and precipitation (P); spermaceti control (Q) and precipitation (R); mono / distearic acid glyceryl control (S) and precipitation (T); monostearic acid glyceryl control (U) and precipitation (V); stearic acid polyethylene glycol glyceride control (W) and precipitation (X).
[0092] 1.1 Rescreening of solid lipids (fatty acids)
[0093] Taking particle size, PDI, encapsulation efficiency and stability as indicators, the types of other reagents were fixed unchanged, and lauric acid, palmitic acid and stearic acid were used as solid lipids, respectively, and Ru-SLN was prepared by the melt emulsification-ultrasound method under item (I). The effects of different solid lipids on Ru-SLN are shown in Table 6.
[0094] Table 6 Effects of different solid lipids on Ru-SLN particle size, PDI, and encapsulation efficiency (n=3)
[0095]
[0096]
[0097] The results showed that after solidification, palmitic acid showed light blue fluorescence, the particle size was (559.973±216.314) nm, the PDI was (0.157±0.053), the encapsulation efficiency was (97.867±0.327)%, and solid precipitated after storage for 2 days, which was milky white; after solidification, lauric acid showed light blue fluorescence, the particle size was (41.584±2.831) nm, the PDI was (0.248±0.011), the encapsulation efficiency was (97.011±1.230)%, and the storage was relatively stable; after solidification, stearic acid showed light blue fluorescence, the particle size was (40.573±0.358) nm, the PDI was (0.236±0.006), the encapsulation efficiency was (96.699±1.424)%, and the storage was relatively stable. The particle size and stability of palmitic acid are poor, while the particle size, PDI and encapsulation efficiency of lauric acid and stearic acid are better. However, since lauric acid has the best solubility for Ru, lauric acid was finally selected as the solid lipid for preparing Ru-SLN.
[0098] 1.2 Screening of drug-to-lipid ratio
[0099] Taking particle size, PDI, encapsulation efficiency and drug loading as indicators, the types of other reagents were fixed and the effects of drug-lipid ratio (ratio of Ru to lauric acid) of 1:0.25, 1:0.5, 1:1, 1:2 and 1:4 on the preparation of Ru-SLN were investigated. The effects of different drug-lipid ratios on Ru-SLN are shown in Table 7.
[0100] Table 7 Effects of different drug-lipid ratios on Ru-SLN particle size, PDI, encapsulation efficiency, and drug loading (n=3)
[0101]
[0102] The results showed that when the drug-lipid ratio was 1:4, it was milky white after solidification, with a large amount of solid precipitated and a large particle size (874.672±555.033) nm, and the encapsulation efficiency and drug loading could not be determined by ultrafiltration centrifugation; when the drug-lipid ratio was 1:0.25, 1:0.5, 1:1, and 1:2, the particle size, PDI, encapsulation efficiency, and drug loading were all good, but when preparing colostrum at 1:0.25 and 1:0.5, a small amount of solid was found to be unmelted. This may be due to the high melting point of Ru (86°C), and the temperature during the preparation of colostrum (75°C) cannot directly melt Ru, so sufficient solid lipids need to be melted first and then dissolve Ru.
[0103] Since the lauric acid content is low when the drug-lipid ratio is 1:0.25 and 1:0.5, Ru cannot be completely dissolved. Finally, 1:1 and 1:2 were selected as the drug-lipid ratios for preparing Ru-SLN. That is, the optimal range of the drug-lipid ratio was 1:1 to 2.
[0104] 2. Preliminary screening of surfactant types
[0105] Taking the solubilizing ability of lauric acid as an index, the effects of 19 surfactants including Tween-20, Tween-40, Tween-60, Tween-80, Span-80, PEG-40 hydrogenated castor oil (CO-40), PEG-60 hydrogenated castor oil (CO-60), EL-10, EL-20, EL-35, EL-40, EL-60, EL-80, RH-40, poloxamer-188, sodium deoxycholate, benzyl-78, TPGS, and sodium taurodeoxycholate on the preparation of Ru-SLN were investigated.
[0106] Accurately weigh 100 mg each of 19 surfactants including Tween-20, Tween-40, Tween-60, Tween-80, Span-80, PEG-40 hydrogenated castor oil, PEG-60 hydrogenated castor oil, EL-10, EL-20, EL-35, EL-40, EL-60, EL-80, RH-40, poloxamer-188, sodium deoxycholate, benzyl-78, TPGS, and sodium taurodeoxycholate, add appropriate amount of ultrapure water, vortex appropriately to fully dissolve and mix the surfactant, and prepare different 1% surfactant solutions; accurately weigh 100 mg of solid lipid lauric acid, add 3 mL of anhydrous ethanol to fully dissolve and mix it to obtain an oil phase; add different 1% surfactant solutions to the oil phase and mix thoroughly, heat in a water bath at 40°C to evaporate and remove anhydrous ethanol, and obtain an emulsified solution. Take an appropriate amount of the emulsified solution and dilute it with ten times ultrapure water to obtain the test solution. The absorbance of the test solution was measured at 510 nm by UV-visible spectrophotometer, and ultrapure water was used as calibration solution. A surfactant absorbance bar graph was drawn with different surfactants as the horizontal coordinate and absorbance as the vertical coordinate, and a surfactant with better solubilization ability for lauric acid was selected.
[0107] The solubilization ability of 19 surfactants on lauric acid is shown in Figure 2 The emulsifying ability of the surfactant is determined by observing the absorbance. The higher the absorbance, the smaller the particle size, the better the emulsifying effect, and the stronger the solubilizing ability.
[0108] The results showed that the solubilization effects of different surfactants on lauric acid were as follows: sodium taurodeoxycholate (0.104±0.034), benzyl-78 (0.117±0.029), PEG-40 hydrogenated castor oil (0.121±0.015), PEG-60 hydrogenated castor oil (0.165±0.082), TPGS (0.166±0.022), RH-40 (0.172±0.150), EL-35 (0.173±0.110), EL-40 (0.210±0.082), E L-60 (0.210±0.082), EL-20 (0.291±0.094), Tween-80 (0.297±0.032), EL-80 (0.327±0.071), Span-80 (0.501±0.072), Tween-60 (0.536±0.240), Tween-40 (0.567±0.353), Tween-20 (0.846±0.082), sodium deoxycholate (1.424±0.679), and EL-10 (2.295±0.033).
[0109] Since PEG-40 hydrogenated castor oil and PEG-60 hydrogenated castor oil are the same type of surfactants, only PEG-40 hydrogenated castor oil with smaller absorbance was selected. Finally, sodium taurodeoxycholate, benzyl alcohol-78, PEG-40 hydrogenated castor oil, and TPGS were selected as surfactants to further prepare Ru-SLN.
[0110] It should be noted that in Figure 2 In the table, each number represents a surfactant: 1: TW-20; 2: TW-40; 3: TW-60; 4: TW-80; 5: EL-10; 6: EL-20; 7: EL-35; 8: EL-40; 9: EL-60; 10: EL-80; 11: PEG-40 hydrogenated castor oil; 12: PEG-60 hydrogenated castor oil; 13: RH-40; 14: SP-80; 15: sodium deoxycholate; 16: sodium taurodeoxycholate; 17: TPGS; 18: benzyl alcohol-78.
[0111] 2.1 Rescreening of surfactant types and selection of dosage
[0112] 2.1.1 Rescreening of surfactant types
[0113] Taking particle size, PDI and encapsulation efficiency as indicators, the types of other reagents were fixed and the effects of sodium taurodeoxycholate, benzyl-78, PEG-40 hydrogenated castor oil and TPGS as surfactants on the preparation of Ru-SLN were further investigated. The effects of different surfactants on Ru-SLN are shown in Table 8.
[0114] Table 8 Effects of different surfactants on Ru-SLN particle size, PDI, and encapsulation efficiency (n=3)
[0115] Surfactant Type Particle size / nm PDI Encapsulation rate / % Sodium taurodeoxycholate 384.086±149.705 0.222±0.087 80.703±7.032 Benzyl-78 28.386±0.956 0.243±0.014 98.830±1.170 PEG-40 Hydrogenated Castor Oil 39.221±0.649 0.243±0.014 97.070±1.733 TPGS 30.722±1.061 0.216±0.021 97.432±1.897
[0116] The results show that sodium taurodeoxycholate solidifies into a colorless transparent solution with a large particle size of (384.086±149.705) nm and a low encapsulation rate of (80.703±7.032)%; benzyl-78 solidifies into a light blue fluorescence with a small particle size of (28.386±0.956) nm, but the particle size tends to increase after being placed for 6 days (58.253±81.990) nm; PEG-40 hydrogenated castor oil and TPGS solidify into a light blue fluorescence with better particle size, PDI and encapsulation rate. However, since PEG-40 hydrogenated castor oil has the best solubilizing ability for lauric acid, the present invention finally selects PEG-40 hydrogenated castor oil as the surfactant for preparing Ru-SLN.
[0117] 2.1.1 Screening of surfactant dosage
[0118] Taking particle size, PDI and encapsulation efficiency as indicators, the types of other reagents were fixed and the effects of different amounts of surfactant on the preparation of Ru-SLN were investigated. The effects of surfactant addition amounts of 50 mg, 150 mg, 450 mg, 750 mg and 1050 mg on Ru-SLN are shown in Table 9.
[0119] Table 9 Effect of different surfactant addition amounts on Ru-SLN particle size, PDI, encapsulation efficiency, and drug loading (n=3)
[0120]
[0121]
[0122] The results showed that with the increase of surfactant, the particle size and drug loading decreased, the encapsulation efficiency increased slightly, and solid precipitation occurred in 50mg and 150mg samples the next day of storage; the particle size, PDI, encapsulation efficiency and drug loading of 450mg, 750mg and 1050mg were better, so the final amount of surfactant selected was 450mg, 750mg and 1050mg.
[0123] 3. Selection of phospholipid types and dosage
[0124] 3.1 Screening of phospholipid types
[0125] Taking particle size, PDI and encapsulation efficiency as indicators, the total types of other reagents were fixed unchanged, and soy lecithin, egg yolk lecithin (Avitor), hydrogenated soy lecithin and egg yolk lecithin (LIPOID) were used as phospholipids, and Ru-SLN was prepared by the melt emulsification-ultrasound method under item (I). The effects of different phospholipids on the preparation of Ru-SLN are shown in Table 10.
[0126] Table 10 Effects of different phospholipids on Ru-SLN particle size, PDI, and encapsulation efficiency (n=3)
[0127]
[0128] The results show that hydrogenated soybean lecithin is milky white after ultrasound, and a large amount of white solid is precipitated after solidification, and the particle size, PDI and encapsulation efficiency cannot be detected; the other phospholipids are relatively clear after solidification, egg yolk lecithin (LIPOID) is a yellow solution, and egg yolk lecithin (Avitor) is light blue fluorescence after solidification, and turns yellow the next day of storage; the particle size, PDI and encapsulation efficiency of the three phospholipids are all excellent. Combined with the appearance and stability, the present invention finally selects soybean lecithin as the phospholipid for preparing Ru-SLN.
[0129] 3.2 Selection of phospholipid dosage
[0130] Taking particle size, PDI, encapsulation efficiency and drug loading as indicators, the addition amount of other reagents was fixed and the effects of different amounts of phospholipids on the preparation of Ru-SLN were investigated. The effects of phospholipid addition amounts of 100 mg, 200 mg, 300 mg, 400 mg and 500 mg on Ru-SLN are shown in Table 11.
[0131] Table 11 Effects of different amounts of phospholipids on Ru-SLN particle size, PDI, encapsulation efficiency, and drug loading (n=3)
[0132] Phospholipids / mg Particle size / nm PDI Encapsulation rate / % Drug loading / % 100 453.888±630.254 0.299±0.116 95.031±0.459 4.453±0.015 200 41.822±2.752 0.245±0.017 96.015±0.647 3.935±0.020 300 45.626±0.679 0.235±0.024 96.188±0.218 3.434±0.028 400 49.574±2.880 0.249±0.016 96.013±0.916 3.075±0.060 500 54.368±2.235 0.259±0.007 95.013±0.724 2.774±0.030
[0133] The results show that when the addition amount is 100 mg, the particle size difference is large (453.888±630.254) nm, the group is not parallel, the PDI is large (0.299±0.116), and floccules are precipitated the next day of storage, which should be the instability of the preparation; except for 100 mg, with the increase of phospholipids, the Ru-SLN particle size is larger. However, since the encapsulation efficiency (95.013±0.724)% and the drug loading (2.774±0.030)% are both low when the addition amount is 500 mg, the present invention finally selects the addition amount of phospholipids to be 200 mg, 300 mg, and 400 mg.
[0134] 4. Screening of Ruxolitinib (Ru) dosage
[0135] Taking particle size, PDI, encapsulation efficiency and drug loading as indicators, the addition amount of other reagents was fixed and the effects of different amounts of Ru on Ru-SLN were investigated. The effects of Ru addition amounts of 50 mg, 60 mg, 70 mg, 80 mg and 90 mg on Ru-SLN are shown in Table 12.
[0136] Table 12 Effect of different Ru addition amounts on Ru-SLN particle size, PDI, encapsulation efficiency, and drug loading (n=3)
[0137] Ru / mg Particle size / nm PDI Encapsulation rate / % Drug loading / % 50 36.683±0.225 0.222±0.014 96.873±0.531 4.218±0.022 60 42.237±0.479 0.248±0.062 97.053±0.178 4.982±0.012 70 39.090±0.262 0.220±0.003 96.922±0.361 5.712±0.020 80 45.323±0.930 0.248±0.009 97.235±0.468 6.441±0.029 90 43.863±4.075 0.224±0.018 95.752±1.721 7.189±0.128
[0138] The results show that all Ru-SLNs exhibit light blue fluorescence after curing, and the drug loading increases with the increase of Ru addition amount; a large amount of white solid precipitates within 2 days of storage at 90 mg, and the preparation is unstable; combined with various indicators, it can be seen that when the Ru addition amount is 80 mg, all indicators are better, so the optimal Ru addition amount is 80 mg.
[0139] 5. Screening of total solution volume
[0140] Taking particle size, PDI, encapsulation efficiency and drug loading as indicators, the addition amount of other reagents was fixed and the effects of different total solution amounts on Ru-SLN were investigated. The effects of total solution amounts of 10 mL, 15 mL, 20 mL, 25 mL and 30 mL on Ru-SLN are shown in Table 13.
[0141] Table 13 Effects of different total solution amounts on Ru-SLN particle size, PDI, encapsulation efficiency, and drug loading
[0142]
[0143] The results show that when the total amount of the solution is 10 mL, it is milky white and turbid after solidification, with a larger particle size (304.817±187.667) nm and a larger PDI (0.322±0.062). The encapsulation efficiency and drug loading cannot be determined by ultrafiltration centrifugation. The particle size, PDI, encapsulation efficiency and drug loading of the remaining total solutions are all excellent. White solid precipitates within 2 days of storage in 15 mL, which is relatively unstable. In order to maximize the drug concentration, the present invention finally selects 20 mL as the total amount of solution for preparing Ru-SLN.
[0144] 6. Orthogonal experiment to optimize the prescription
[0145] Orthogonal experimental design was established with PEG-40 hydrogenated castor oil addition amount A (750 mg, 900 mg, 1050 mg), soybean lecithin addition amount B (200 mg, 300 mg, 400 mg), and Ru addition amount C (60 mg, 70 mg, 80 mg) as factors and levels. The L9 (33) orthogonal design table was used for prescription screening, and orthogonal experiments were carried out with encapsulation efficiency and drug loading as evaluation indicators to optimize and screen the optimal prescription. The orthogonal design factor level table is shown in Table 14.
[0146] Table 14 Factor levels of orthogonal design
[0147]
[0148] Encapsulation rate and drug loading are important indicators for evaluating whether a drug delivery system is qualified and effective. This experiment divides the weights of encapsulation rate and drug loading equally and scores the results of the orthogonal experiment. The specific scoring formula is: Encapsulation rate score = (encapsulation rate-Min encapsulation rate) / (Max encapsulation rate-Min encapsulation rate)*10; Drug loading score = (Drug loading-Min drug loading) / (Max drug loading-Min drug loading)*10; Comprehensive score = 0.5*encapsulation rate score+0.5*drug loading score. The scoring results are shown in Table 15.
[0149] Table 15L9(3 3 )Orthogonal experimental results
[0150]
[0151]
[0152] Note: K1, K2, K3 represent the average scores of each factor, and R represents the difference (range) between the maximum level experimental value and the minimum level experimental value.
[0153] In order to avoid experimental errors, the results were subjected to variance analysis. The results are shown in Table 16. The sum of squared deviations reflects the degree of influence of each factor on the index. The larger the sum of squared variances, the greater the degree of influence.
[0154] Table 16 Orthogonal experiment variance analysis table
[0155] Sum of Squared Deviations Degrees of Freedom F Ratio Significant P A 8.252 2 0.478 0.676 B 5.625 2 0.326 0.754 C 13.896 2 0.806 0.554 error 17.249
[0156] The results showed that the order of influence of the three factors on the encapsulation efficiency and drug loading was C>A>B, and there was no significant difference among the factors (P>0.05). The results of the level analysis of each factor were A1>A2>A3, B2>B1>B3, C3>C2>C1. Therefore, the optimal prescription was A1B2C3, i.e. 750 mg PEG-40 hydrogenated castor oil, 300 mg soy lecithin, and 80 mg Ru.
[0157] 7. Prescription and process validation
[0158] In summary, the optimal formula is: accurately weigh 80 mg of Ru and 80 mg of lauric acid and place them in a 50 mL conical beaker, heat and melt them at 75 ° C and 1000 min / r under magnetic stirring to obtain the oil phase; accurately weigh 750 mg of PEG-40 hydrogenated castor oil and 300 mg of soybean lecithin and place them in a 50 mL EP tube, add 15 mL of ultrapure water and stir them thoroughly at 75 ° C to dissolve and mix the surfactant and phospholipid to obtain the water phase. Slowly drip the water phase into the oil phase at 1000 min / r and 75 ° C for 5 min, and continue stirring for 20 min to obtain colostrum; ultrasonicate the colostrum at room temperature (power: 80%, on: 5s, off: 5s) for 10 min, then place it in an ice bath to solidify for 10 min, then adjust the volume to 20 mL, and filter through a 0.22 μm micropore filter to obtain the sample Ru-SLN.
[0159] The appearance of the above sample Ru-SLN is compared with that of ultrapure water. Figure 3 As shown, the particle size is Figure 4 ,exist Figure 3 In the figure, the left side shows the appearance of ultrapure water, and the right side shows the appearance of the sample Ru-SLN. The results show that Ru-SLN is clear and transparent, with a light blue fluorescence and is relatively uniform.
[0160] Three batches of samples were prepared in parallel, and the results of particle size, encapsulation efficiency and drug loading are shown in Table 17.
[0161] Table 17 Particle size, PDI, encapsulation efficiency and drug loading results of three batches of Ru-SLN
[0162] Sample No. Particle size (nm) PDI Encapsulation rate (%) Drug loading (%) 1 38.753 0.206 98.797 8.253 2 45.415 0.353 95.031 4.156 3 40.532 0.185 97.205 6.678 Mean ± SD 41.584±2.831 0.248±0.011 97.011±1.230 6.349±0.080
[0163] The results show that the preparation process of the present invention is stable and reliable, and the Ru-SLN sample prepared by the process of the present invention has a small particle size, a moderate PDI, and a high encapsulation efficiency and drug loading.
[0164] 8. Determination of Ru-SLN particle size and PDI
[0165] The particle size and polydispersity index (PDI) of Ru-SLN were measured by a particle size analyzer.
[0166] 9. Determination of encapsulation efficiency and drug loading
[0167] 9.1 Method for determination of encapsulation efficiency
[0168] Free and encapsulated drugs were separated by ultrafiltration centrifugation. Accurately measure 1 mL of Ru-SLN in a 10K ultrafiltration centrifuge tube, centrifuge at 10000 min / r for 10 min, take the ultrafiltrate and filter it through a 0.22 μm microporous filter membrane, take the filtrate, inject it into a high-performance liquid chromatograph, measure it, record the peak area, and calculate W free; accurately measure 1 mL of Ru-SLN in a 10 mL volumetric flask, add an appropriate amount of acetonitrile for ultrasonic demulsification and dilute to the scale with the mobile phase, shake well, filter it through a 0.22 μm microporous filter membrane, take the filtrate, inject it into a high-performance liquid chromatograph, measure it, record the peak area, and calculate W total. The encapsulation rate calculation formula is as follows:
[0169] Encapsulation efficiency = [((W total - W free) / W total] × 100%
[0170] 9.2 Determination of drug loading
[0171] Ru-SLN was freeze-dried by freeze drying and the drug loading was calculated. Ru-SLN was pre-frozen at -20°C and freeze-dried in a freeze dryer. The total weight W was weighed after drying. The drug loading was calculated as follows:
[0172] Drug loading = W 游离 / W total × 100%
[0173] 2. Ru-SLN in vitro release test
[0174] The in vitro release of Ru-SLN was determined by the dialysis bag method. The specific steps are as follows:
[0175] (1) Preparation of dialysis bag: Cut a dialysis bag (3500D) of appropriate length and activate it in boiling purified water for 10 minutes. Before use, check for leaks in the dialysis bag. Tighten one end of the dialysis bag with a nylon rope, add a small amount of purified water into the dialysis bag, and observe the leakage of the dialysis bag.
[0176] (2) Preparation of release medium: 11 g of sodium dodecyl sulfate (SDS) was accurately weighed into a 1000 mL beaker and dissolved in 550 mL of PBS (pH = 7.4) buffer to obtain a PBS release medium containing 2% SDS.
[0177] (3) In vitro release determination: 2 mL of Ru-SLN was placed in a dialysis bag, which was then tightened with a nylon rope and placed in an EP tube containing 30 mL of release medium. The tube was oscillated in an air bath constant temperature oscillator (T = 32 °C, speed = 120 min / rpm). 1 mL of release medium was drawn at different time periods (0, 0.5, 1, 2, 4, 6, 12, 24, 36, 48, 72 h) and fresh release medium was added in time. The samples drawn at different time periods were mixed with an equal volume of acetonitrile, filtered through a 0.22 μm microporous membrane, and the content was determined by HPLC. The peak area was recorded and the cumulative release amount (mg) was calculated. The cumulative release rate Q n The release curve is drawn with Q as the ordinate and time T as the abscissa. n The calculation formula of (%) is as follows:
[0178]
[0179] Where Q n (%) is the cumulative release at the nth time point; C n is the drug concentration at the nth time point; V is the volume of the release medium; C i V is the drug concentration in the release medium at the (n-1)th time point; i is the sampling volume and mtotal is the total amount of drug added to the sample.
[0180] The relationship between the release rate of Ru-SLN in vitro and time is as follows Figure 5 As shown in the figure, the release rate of Ru-SLN in 24h is (83.23±5.40)%, and then the release effect tends to be flat. Ru-SLN can release more than 80% of Ru within 24h, which can ensure that the effective drug concentration is maintained in the cells and stratum corneum, which is conducive to the efficacy of the drug.
[0181] 3. Comparative test of in vitro percutaneous permeability of Ru-Cream and Ru-SLN
[0182] The Franz diffusion cell method was used for determination. The specific steps are as follows:
[0183] (1) Preparation of rat skin: SD rats (about 210 g) were anesthetized with 10% chloral hydrate, their abdominal hair was shaved with an electric razor, and they were killed by cervical dislocation, and their skin was peeled off. The skin was spread on a clean foam box, and the excess fat and blood vessels were carefully removed with scissors and tweezers, and then rinsed with PBS (pH = 7.4), dried with filter paper, wrapped in plastic wrap, and stored in a -20°C refrigerator for later use. Before the experiment, the skin was taken out of the refrigerator and allowed to cool to room temperature, and then soaked in physiological saline for 30 minutes for hydration.
[0184] (2) Determination of in vitro permeation: Select intact skin, cut it into appropriate sizes and fix it between Franz diffusion cells, keeping the stratum corneum facing the supply cell and the dermis facing the receiving cell. Weigh 250 mg of Ru-Cream and Ru-SLN respectively and apply them evenly on the isolated mouse skin. Fill the receiving cell with a receiving medium containing 20% ethanol-PBS. Add a rotor and exhaust the air between the mouse skin and the liquid surface to ensure full contact between the two. Set the speed of the Franz diffusion cell to 350 min / rpm and the temperature to (32±0.5)°C. Absorb 0.5 mL of the receiving medium at 1, 2, 4, 8, 12, and 24 h, and replenish fresh receiving medium at isothermal and isovolumetric conditions in a timely manner. Filter the receiving medium at different time periods through a 0.22 μm microporous filter membrane, determine the content by HPLC, and calculate the cumulative transdermal amount per unit skin area Q n (μg·cm-2), and the cumulative transdermal amount per unit skin area is Q n The permeation curve is drawn with Q as the ordinate and time T as the abscissa. n (μg·cm-2) is calculated as follows:
[0185]
[0186] Among them C n is the drug concentration at the nth time point; V is the volume of the receiving medium; Ci is the cumulative drug concentration in the release medium at the (n-1)th time point; V i is the sampling volume, and A is the effective transdermal area.
[0187] (3) Determination of in vitro retention: After the transdermal experiment, the skin was removed from the diffusion cell, and the Ru-Cream and Ru-SLN remaining in the epidermis were rinsed with pure water. The skin was cut into pieces and placed in a 10mL EP tube. 3mL of acetonitrile was added and ultrasonicated in a cell disruptor for 2min (power 300w, on: 5s, off: 5s), and then placed in an ultrasonic cleaner for 1h to completely extract the drug retained in the skin. The extract was transferred to a 5mL volumetric flask, washed with a small amount of mobile phase several times and diluted to the scale line, filtered through a 0.22μm microporous membrane, and the content was determined by HPLC to calculate the drug skin retention.
[0188] The in vitro skin permeation and skin retention of Ru-Cream and Ru-SLN were Figure 6 , Figure 7 as well as Figure 8As shown in the figure, compared with the homemade traditional Ru-Cream, the skin permeation of Ru can be significantly increased after Ru is prepared into SLN ((35.99±3.93)μg·cm-2)(p≤0.01), and Ru-SLN slowly penetrates within 24 hours, which conforms to the first-order kinetic equation (R2=0.9956). In terms of skin retention, there is no significant difference between Ru-SLN ((11.70±5.94)μg·cm-2) and Ru-Cream ((8.93±2.12)μg·cm-2). In terms of the total amount of skin permeation retention, the overall transdermal utilization rate of Ru-SLN is higher than that of Ru-Cream. Higher skin permeation and retention may improve the therapeutic effect of Ru as a transdermal drug delivery preparation. Therefore, Ru-SLN has the potential to be superior to Ru-Cream in the treatment of vitiligo.
[0189] 4. Pharmacodynamics of Ru-SLN
[0190] To investigate the vitiligo treatment effect of Ru-SLN, the steps are as follows:
[0191] (1) Preparation of vitiligo animal model: A vitiligo mouse model was established using 40% monobenzone cream combined with tretinoin cream. Four-week-old male C57BL / 6 mice were anesthetized by intraperitoneal injection of 10% chloral hydrate (0.35 mL / 100 g), and the hair on the back skin was shaved to expose a skin area of approximately 2×2 cm. 50 mg of 40% monobenzone cream and 20 mg of tretinoin cream were applied to the exposed skin once every three days for 14 days. During this period, the mice could eat and drink normally.
[0192] (2) Investigation of the therapeutic effect of Ru-SLN: After modeling, the vitiligo mice were divided into two groups according to the vitiligo lesions: a vitiligo model group and a Ru-SLN group, as well as a normal group of normal mice. The normal group and the model group were given saline twice a day to apply to the depilated area on the back of the mice, with an application amount of about 200 mg; the Ru-SLN group was given Ru-SLN suspension twice a day to apply to the depilated area on the back of the mice, with an application amount of about 200 mg. The back of the mice was photographed after isoflurane gas anesthesia on days 0, 1, 3, 5, 7, 10, and 14 of modeling to observe the vitiligo lesions in different groups; the mice were weighed, and the weight changes of mice in different groups were counted to investigate the safety of the drug.
[0193] The weight changes of mice after 14 days of treatment were as follows Fig. 9 As shown, during the treatment period, there was no significant difference in body weight between the vitiligo group and the normal group, indicating that vitiligo may not have a significant effect on the weight changes of mice; there was no significant difference in the body weight of the Ru-SLN group and the normal group, indicating that the Ru-SLN prescription did not affect the weight changes of mice and was relatively safe.
[0194] Changes in vitiligo areas in mice after 14 days of treatment Fig.10 As shown in the figure, vitiligo is skin pigmentation caused by lack of epidermal pigment. The human skin is not covered with a lot of hair, and melanocytes are located in the basal layer rather than hair follicles. Melanin formed by melanocytes is transferred to keratinocytes, resulting in skin coloration. However, the epidermis of mice has low pigment content. The epidermis of C57 / BL6 mice lacks melanocytes, and most melanocytes are located in hair follicles. Therefore, after depigmentation, the most obvious phenomenon is the whitening of hair, rather than the appearance of white spots on the epidermis. After hair removal on day 0, the back skin of mice in the normal group was gray-brown and the villi were black. Black hair began to grow in the hair removal area after the first day of treatment, and the grown black hair completely covered the hair removal area on the 14th day of treatment. On day 0, the skin of the hair removal area on the back of all mice in the modeling group was paler, and all mice had white hair growth to varying degrees. On day 14, although a small amount of black hair was generated in the hair removal area on the back of the vitiligo model group, pale skin and white hair could still be clearly observed. However, on day 14, the upper half of the back of the Ru-SLN group was covered with black hair, and most of the hair removal area was covered with black hair, indicating that preparing Ru as nanoparticles can improve the efficacy of the drug.
[0195] The above is only a preferred embodiment of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A Ruxolitinib solid lipid nanoparticle, characterized in that: The nanoparticles have ruxolitinib as the core and are coated with a coating material on the surface, wherein the coating material includes a fatty acid material, a phospholipid material, and a surfactant, wherein the mass ratio of ruxolitinib, the fatty acid material, the phospholipid material, and the surfactant is 1:(1-2):(2.5-5):(5-14) by mass ratio; The preparation method of the Ruxolitinib solid lipid nanoparticles comprises the following steps: Step 1: heating and stirring ruxolitinib and fatty acid materials at 75° C. to melt to obtain an oil phase; Step 2: dissolving and mixing the phospholipid material and the surfactant in deionized water to obtain an aqueous phase; Step 3: After the water phase is heated to the same temperature as the oil phase, it is slowly dripped into the oil phase and stirred at a constant rate to obtain colostrum; wherein the dripping time is 0 to 10 minutes and the stirring time is 15 to 25 minutes; Step 4: After ultrasonicating the colostrum at room temperature, solidify it in an ice bath to obtain ruxolitinib solid lipid nanoparticles; wherein the total amount of colostrum is 20-30 mL, the ultrasonication time is 5-15 min, and the solidification time is 0-20 min; Wherein, the fatty acid material is lauric acid or stearic acid; the phospholipid material is soybean lecithin or egg yolk lecithin; and the surfactant is PEG-40 hydrogenated castor oil or TPGS.